A population-based cohort study for presence of ulceration among cutaneous malignant melanoma subgroups of patients - Li, Xinrui; Li, Zichao; Yi, Xiaowei; Gao, Xianchun; Yang, Zhe; Huang, Xingning; Ma, Sijie; Ma, Tianyuan; Deng, Ziyi; Shang, Lei; Jian, Zhe (Frontiers in Oncology, 2022)
Abstract Background: Observational studies suggest that ulceration is considered to be a negative prognostic factor for cutaneous melanoma. However, the impact of ulceration over different subgroups (e.g. AJCC Stage, thickness level) are controversial and its true causal effect on survival is lack of studies in the view of treating ulceration as an exposure. Objective: To explore the true causal effect of ulceration on melanoma’s survival by adopting a combination of methods to discover proper adjustment set and confirming its correctness through a variety of means. Methods: A minimal sufficient adjustment set (MSAS) was found using directed acyclic graphs (DAG) to adjust the effect of causality. Sensitivity analysis was conducted to diagnose potential confounders in addition to MSAS. Cox models were built to analyze the causality in-depth and the model was validated using a novel method. Lastly, stratified effects of ulceration were examined to illustrate its impact within subgroups. Results: Hazard ratio (HR) of ulceration after adjustment by MSAS variables was 1.99 (95% CI=1.88-2.09). The sensitivity analysis of propensity score matching and E-value both demonstrated that variables other than MSAS do not have great influence on ulceration and MSS relationship. The HR of ulceration in AJCC Stage, thickness level, invasion level and tumor extension were all monotonically decreased from 5.76 to 1.57, 4.03 to 1.78, 2.75 to 1.78 and 2.65 to 1.71 respectively. Conclusion: Ulceration in all subgroups were shown to have a significantly negative impact on MSS and its magnitude of effect was monotonically decreased as the disease progressed. The true effect of ulceration can be adjusted by MSAS and its correctness was validated through a variety of approaches.